The Predictors for Maternal Self-efficacy in Early Parenthood - Elham Azmoude; Farzaneh Jafarnejade; Seyed Reza Mazlom (Mashhad University of Medical Sciences, 2015)
Background & aim: Many parents do not believe in their ability to fulfill their parental responsibilities. Parental self-efficacy is crucial to parents' sense of well-being and is considered a predictor for quality of life. However, evidence is scarce on the factors that influence parents' perception of efficacy. Therefore, this study aimed to investigate the predictors for parental self-efficacy in the early postpartum period. Methods:This descriptive analytical study was conducted on 150 primiparous women referring to the health care centers of Mashhad during their early postpartum months. For data collection, we used demographic questionnaires, Bates' Infant Characteristics Questionnaire (ICQ), Scale of Perceived Social Support, Reece's parent expectations survey (PES), and Edinburgh Postnatal Depression Scale (EPDS). For data analysis, independent T-test, one-way ANOVA, Pearson's correlation coefficient, and stepwise regression were performed, using SPSS version 16. Results: In this study, a significant association was observed between self-efficacy scores and the parents' income, educational status, depression, and infant's gender. Furthermore, there was a significant correlation between self-efficacy scores and infant's characteristics, mother's satisfaction with childbirth experience, perceived support from friends, infant's perceived temperament, infant's gender, mother's educational level, and depression, which could predict 26.1% of parental self-efficacy. Conclusion: According to the results of this study, the most significant predictors of maternal self-efficacy during the early postpartum months were maternal depression and educational status, infant's gender, and infant's characteristics.